Oxford Mini Study Spanish Dictionary - Rollin, Nicholas (Oxford University Press, 2004)
This new edition has been expanded to include 800 new headwords with particular attention paid to new terminology for IT and Spanish culture and customs. It is updated for 2004 with over 800 new entries covering...